Diferenciácia regionálneho rozvoja Slovenska a jej sociálno – ekonomické dopady - Bilá, Anna (Univerzita Pardubice, 2006)
This conference paper deals with the regional development problems of Slovakia emphasizing the presentation of its developmental differentiation after the entry into European Union (EU). It depicts the regional differentiation problems inward the new EU member states as well as the European regional policy changes. It presents the regional development of Slovakia in more extensive social-economical and social-spatial changes of society trend within the Transformation time period. The realized analysis demonstrate the considerable regional disparity both in European Union both in Slovakia. Strategically, the regional policy should be aimed at the solution of this state in the individual member states. The state financial aid forms the significant part of regional policy. In conclusion, this paper compare the region disposal and the developmental trend of Slovakia with the information society development conditions.
Keywords: regional differentiation; European regional policy; regional competitiveness; strategic trend of regional policy; state financial aid; social – economical impacts